2019
DOI: 10.1002/14651858.cd001534.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term antibiotics for preventing recurrent urinary tract infection in children

Abstract: Long-term antibiotics for preventing recurrent urinary tract infection in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 89 publications
0
38
0
4
Order By: Relevance
“…Nitrofurantoin is an antibiotic medicament often used in the treatment of recurrent urinary tract infections as the urinary excretion rate is high. Recent studies have questioned the efficacy of antibiotics in the prevention of recurrent urinary tract infections and secondary renal injury in children [ 7 ]. In a recent paper in the Lancet, the authors concluded that “a trial using antimicrobial prophylaxis in children with several recurrent episodes of acute pyelonephritis is warranted” [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrofurantoin is an antibiotic medicament often used in the treatment of recurrent urinary tract infections as the urinary excretion rate is high. Recent studies have questioned the efficacy of antibiotics in the prevention of recurrent urinary tract infections and secondary renal injury in children [ 7 ]. In a recent paper in the Lancet, the authors concluded that “a trial using antimicrobial prophylaxis in children with several recurrent episodes of acute pyelonephritis is warranted” [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Up to 30% of these children will experience at least one recurrence within 6-12 months. 2,3 While 3-15% of children with a first UTI will show renal parenchymal scarring within 1-2 years of their first UTI, [4][5][6][7] the risk of acquired chronic kidney disease remains low. 5,8 An rUTI can be defined as a repeated presentation with separate episodes of cystitis, pyelonephritis or urosepsis.…”
Section: Recurrent Urinary Tract Infectionsmentioning
confidence: 99%
“…Durch eine gezielte Anamnese kann die Wahrscheinlichkeit, dass es sich um einen HWI durch Erreger mit speziellen Resistenzen handelt, deutlich erhöht werden. Meist handelt es sich dabei um Kinder mit angeborenen Fehlbildungen der Harnwege unter einer antibiotischen Prophylaxe oder um Kinder mit wiederholter Antibiotikaexposition und Krankenhausaufenthalten in den letzten Monaten [22].…”
Section: Ambulant Erworbene Stationär Behandelte Harnwegsinfektion (unclassified